Internet core protocols : the definitive guide - Hall, Eric A. (O'Reilly, 2000)
"Internet Core Protocols is the first in a series of books that discuss the Internet protocols from the standpoint of a network administrator. Eric Hall goes into detail about how each protocol works, what can go wrong, and what problems you typically face. He shows detailed examples of the protocols in action, including many complete packet traces. If you spend your days (and nights) working on real networks, you'll want this book at your side." "This book covers the core protocols that provide the underpinnings of any IP network: IP, TCP, UDP, ARP, ICMP, and IGMP. It also covers the standardization process and IP addressing. The accompanying CD includes Shomiti's Surveyor Lite, and the complete text of all the RFCs. Future books in the series will cover application protocols and other topics. Together, you'll have everything you need to understand your network, figure out what's going on, and get it running again."--Jacket